Proposta e avaliação da combinação de uma metodologia ágil e GQM+strategies para o desenvolvimento de aplicações de business intelligence dirigido à estratégia - Lima, Adriano Silva de (2017)
The competition scenario among companies in the various market niches, marked by the constant need for growth, has leveraged the strategic investment in Information Technology, aiming at reducing its operational costs and achieving the business objectives. In this context, the use of Business Intelligence (BI) has been one of the main solutions for adding value to the company. However, it is necessary to characterize and propose improvements for the use of this type of application in the market, since many companies have found difficulties and losses in their implementation, mainly, from the strategic point of view. The objective of this dissertation was to propose and evaluate a method that combines the GQM + Strategies approach with a methodology of agile development of Business Intelligence applications, aiming to guarantee the strategic alignment. For characterization, a systematic mapping and a survey were carried out that identified and confirmed the need for investments by the industry in experiments that evaluate development methodologies, as well as strategic alignment methodologies, as an indispensable part of projects of this type. For evaluation, a case study was carried out using the method proposed in a Latin American multinational company in the retail market. The results provided evidence that it is possible to integrate the strategic alignment approach adopted with a BI application development methodology